PENGARUH INFLASI, SUKU BUNGA, LIKUIDITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Hendayana, Yayan; Riyanti, Nopita (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
This study aims to determine the effect of inflation (Consumer Price Index), Interest Rate (BI Rate), Liquidity Ratio (Current Ratio) and Leverage Ratio (Debt to Equity Ratio) on Company Value (Price to Book Value). The seals used in this study were Plantation Sub-Sector Companies listed on the Indonesia Stock Exchange and published financial statements in 2012-2017 with 15 sample companies using the purposive sampling method. The independent variables of this study are Inflation as measured by the Consumer Price Index (CPI), Interest Rates as measured by the BI Rate, Liquidity Ratio as measured by Current Ratio (CR) and Leverage Ratio as measured by Debt to Equity Ratio (DER). The dependent variable of this study is the Company Value measured by Price to Book Value (PBV). The results show that Inflation (Consumer Price Index), Interest Rate (BI Rate), Liquidity Ratio (Current Ratio) and Leverage Ratio (Debt to Equity Ratio) a have significant effect on Company Value (Price to Book Value).